OG716: Designing a fit-for-purpose lantibiotic for the treatment of Clostridium difficile infections. - Johan A Kers; Anthony W DeFusco; Jae H Park; Jin Xu; Mark E Pulse; William J Weiss; Martin Handfield (PLoS ONE)
Lantibiotics continue to offer an untapped pipeline for the development of novel antibiotics. We report here the discovery of a novel lantibiotic for the treatment of C. difficile infection (CDI). The leads were selected from a library of over 300 multiple substitution variants of the lantibiotic Mutacin 1140 (MU1140). Top performers were selected based on testing for superior potency, solubility, manufacturability, and physicochemical and/or metabolic stability in biologically-relevant systems. The best performers in vitro were further evaluated orally in the Golden Syrian hamster model of CDAD. In vivo testing ultimately identified OG716 as the lead compound, which conferred 100% survival and no relapse at 3 weeks post infection. MU1140-derived variants are particularly attractive for further clinical development considering their novel mechanism of action.